2019
DOI: 10.3390/educsci9040262
|View full text |Cite
|
Sign up to set email alerts
|

FrogVLE Application in Science Teaching in Secondary Schools in North Malaysia: Teachers’ Perspective

Abstract: The frogVLE application was launched in Malaysia to provide a virtual learning environment in order to produce competitive and relevant students in the 21st century. As science is one of the most important subjects for the development of a nation, the perspective of teachers as policy implementers should be taken into account in ensuring that the desire is achieved. Hence, this study aimed to investigate the level of application of frogVLE in secondary school science teaching in the northern peninsular of Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Previous studies found that inadequate number of computers, slow access to Frog VLE applications and Internet access problems were among the infrastructure problems faced by the Malaysian school institutions [39]. This finding is also consistent with another studies by Cheok and Wong [40] which also found that nearly all teachers complained the poor Internet connection and facilities as the greatest barrier in implementing e-learning.…”
Section: Organizational Contextsupporting
confidence: 88%
“…Previous studies found that inadequate number of computers, slow access to Frog VLE applications and Internet access problems were among the infrastructure problems faced by the Malaysian school institutions [39]. This finding is also consistent with another studies by Cheok and Wong [40] which also found that nearly all teachers complained the poor Internet connection and facilities as the greatest barrier in implementing e-learning.…”
Section: Organizational Contextsupporting
confidence: 88%
“…Moreover, it is worth noting that the scenario of substituting face-to-face education entirely with online education as a pedagogical strategy to ensure education continuation has never happened in Malaysia before. Therefore, the previous researches in online learning mostly focused on blended learning (Ramli & Saleh, 2019;Awang et al, 2018;Cheok, Wong, Ayub, & Mahmud, 2017;Hashim, Nasri, & Mustafa, 2016). Thus, this paper represents a novel research that focuses on challenges faced by teachers in preparing for full time online T&L during the school closure in conjunction with MCO.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality technology infrastructure should be prioritized as recommended by UNESCO and OECD to ensure education continuation using the online learning platforms (UNESCO, 2020; Reimers & Schleicher, 2020). However, this issue has not been resolved satisfactorily since the utilisation of VLE-Frog for learning management system (Ramli & Saleh, 2019;Awang et al, 2018). Zhang et al, (2020); and Akbulut et al (2020) reported the access to technology as the most prevalent challenge that arose in their respective study.…”
Section: Technological Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The instructor is in charge of conducting effective instruction and standing in for parents at school. (Ramli and Saleh, 2019) Teachers must exhibit positive qualities and attitudes for their pupils to Learning is essentially an activity that includes a teacher and students in a setting designed to change behavior for the better. Learning can also be seen as an attempt made by teachers to support their charges in learning in accordance with their needs, abilities, and interests.…”
Section: Introductionmentioning
confidence: 99%